The Role of Chinese Ethnic in Grebeg Sudiro: A Historical Perspective - Azzahra, Alyssa; Puspitasari, Ayu (Confucius Institute Universitas Sebelas Maret, 2023)
The dynamics of ethnic Chinese life in Indonesia have been a part of historical civilization since ancient times. The involvement of ethnic Chinese is sometimes rarely highlighted by the public, even though there are various roles of ethnic Chinese in the traditions that exist in Indonesia. This research aims to examine the role of ethnic Chinese in Grebeg Sudiro from a historical perspective. This research is based on a literature study with data obtained from various books, journals, and theses to find out the role of ethnic Chinese in Indonesia in the Grebeg Sudiro tradition. The results show this tradition exists in the Central Java region, especially in Surakarta. The ethnic Chinese in this tradition present their cultural heritage and foster a sense of unity and tolerance within the Javanese community. This tradition represents the beauty of diversity and wealth from different backgrounds. It not only shows the role of ethnic Chinese but also shows the symbolism between Javanese and Chinese culture. The awareness of the Javanese community itself can produce a form of diversity in the form of the Grebeg Sudiro tradition.